Empowering Non-Formal Education Policy on Life Skills and Its Implications on People Welfare - Moh. Alifuddin (Journal of Education and Learning (EduLearn), 2017)
The non-formal education policy in responding to the life skills needs of learners has been anticipated by the issuance of some products of legal regulations concerning the non-formal education. Life skills education was explicitly mentioned in legislation, but its implementation has not been in line with the expectations. In practice, many training institutions were only responsible for the output without even trying to channel or hire the students after graduation. The curriculum developed referred to the national standard curriculum by adding local content. Welfare could be easily obtained because the alumni got jobs after completing their skill training. Thus, the life skills education developed was able to give positive implications, especially for the welfare of its alumni and their families